MicroRNA-132 suppresses cell proliferation in human breast cancer by directly targeting FOXA1 - WANG Dan; REN Jin; REN Hui; FU Jin-ling; YU Dan (Acta Pharmacologica Sinica, 2017)
Abstract Dysregulation of microRNAs (miRNAs) has been implicated in cancer. Recently, miR-132 has been reported to be downregulated in the tissues of patients with breast cancer. In this study, we investigated the functional role of miR-132 and its direct target FOXA1 in breast cancer cells. In 30 human breast cancer tissues, FOXA1 was significantly overexpressed and negatively correlated with miR-132 expression. A bioinformatics analysis suggested that FOXA1 was a potential target of miR-132. Furthermore, dual luciferase reporter assays revealed that miR-132 dose-dependently inhibited the luciferase activity of the wt 3’UTR of FOXA1 rather than the mut 3’UTR of FOXA1 in human MDA-MB-468 and SK-BR3 breast cancer cells. Moreover, ectopic miR-132 expression significantly inhibited FOXA1 protein expression, whereas miR-132 knockdown promoted FOXA1 expression in the breast cancer cells. Ectopic miR-132 expression also suppressed proliferation of the breast cancer cells, whereas miR-132 knockdown promoted proliferation of the breast cancer cells, which was reversed by knockdown of FOXA1 expression. We conclude that MiR-132 suppresses proliferation of breast cancer cells at least partially though inhibition of FOXA1. These results suggest that miR-132 and FOXA1 may be potential biomarkers or therapeutic targets in breast cancer.